Parmalat USA turnaround - Shein, James B., 1942- (SAGE Knowledge. Cases., 2008)
The case explains the financial fraud committed by Parmalat and the measures used by Paramalat USA (a milk bottler and supplier) to turn the company around and prevent the company being sold off at a huge loss for its creditors.